Van zwijgcultuur naar zerotolerancebeleid - Jacques Schenderling (Religie & Samenleving)
The handling of complaints about sexual abuse of minors has troubled the Catholic Church in many countries for several decades. An important issue is the allegation that the church tried to hide abuse and to leave perpetrators without punishment. The commission that investigated the sexual abuse of minors in the Roman Catholic Church in the Netherlands (the Deetman Commission) is ambiguous in its answer to the question whether the church fostered a ‘culture of silence’ or not. Examination of the available evidence leads to the conclusion that external transparency had no priority, although pastoral, therapeutic and disciplinary measures were taken to stop abuse. These measures, however, often reinforced the already existing culture of silence. The recently introduced zero-tolerance policy of the church seems to promote external transparency, but it also raises new questions.